2016
DOI: 10.1038/srep32080
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive MRI Assessments of Tissue Microstructures and Macromolecules in the Eye upon Biomechanical or Biochemical Modulation

Abstract: The microstructural organization and composition of the corneoscleral shell (CSS) determine the biomechanical behavior of the eye, and are important in diseases such as glaucoma and myopia. However, limited techniques can assess these properties globally, non-invasively and quantitatively. In this study, we hypothesized that multi-modal magnetic resonance imaging (MRI) can reveal the effects of biomechanical or biochemical modulation on CSS. Upon intraocular pressure (IOP) elevation, CSS appeared hyperintense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 70 publications
1
23
0
Order By: Relevance
“… 24 26 , 34 However, analysis of this effect is outside the scope of this article. Also, recent studies 40 , 41 have shown the presence of the magic angle effect in the corneoscleral shell in MRI, where fibrous microstructure of the sclera is resolved at the magic angle. We did not observe this effect in our images, likely because of the relatively low in-plane and slice resolutions (1 × 1 × 8 mm 3 ) of our scans causing T2* intravoxel dephasing, point spread function (PSF) broadening, as well as partial voluming.…”
Section: Discussionmentioning
confidence: 97%
“… 24 26 , 34 However, analysis of this effect is outside the scope of this article. Also, recent studies 40 , 41 have shown the presence of the magic angle effect in the corneoscleral shell in MRI, where fibrous microstructure of the sclera is resolved at the magic angle. We did not observe this effect in our images, likely because of the relatively low in-plane and slice resolutions (1 × 1 × 8 mm 3 ) of our scans causing T2* intravoxel dephasing, point spread function (PSF) broadening, as well as partial voluming.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, we have used micro-MRI, with in-plane resolution under 30 μm, to examine the collagen microstructure of the optic nerve head and lamina cribrosa using magic angle enhancement (Ho et al, 2014b). More recently, we used a multi-modal MRI approach, consisting of T2-weighted MRI, diffusion tensor MRI and magnetization transfer MRI to study the effects of glycosaminoglycan content and IOP in rat eyes (Ho et al, 2016). This study is the first to demonstrate the use of high-field MRI for measuring whole globe deformations and local deformation of the scleral canal during a controlled inflation test and from a single scan in a large animal model.…”
Section: Discussionmentioning
confidence: 99%
“…IOP was varied by changing the height of PBS in a gravity perfusion system as previously described (Ho et al, 2016; Ho et al, 2014b) and monitored by a pressure transducer designed for MRI applications with a sensitivity of 1 mmHg (BIOPAC Systems, Goleta, CA, USA). Eyes were suspended in hydrogel in an open container, as we have described previously, to prevent the application of external forces (Ho et al, 2016). The same eyes were scanned serially under increasing levels of IOP: 0 mmHg, 10 mmHg, 20 mmHg, or 40 mmHg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we hypothesize that the visual pathway is altered in the early stage of STZ–induced experimental diabetes, and such alterations can be revealed non-invasively by in vivo multi-modal magnetic resonance imaging (MRI). In vivo MRI has been increasingly employed at high magnetic field strengths to evaluate the rodent eye and brain's visual system in health and disease [ 19 26 ]. In this study, we used diffusion tensor MRI (DTI) at 7 Tesla to evaluate the white matter integrity along the visual pathway [ 25 , 27 , 28 ] of STZ-induced diabetic rats and sham control rats.…”
Section: Introductionmentioning
confidence: 99%